PELATIHAN CHATGPT UNTUK MENINGKATKAN KEMAMPUAN PUBLIKASI INSTANT WEBSITE DESA LAEHUWA - Putri Mareta Puspitasari; Retno Waluyo; Ika Romadoni Yunita (Nusantara Hasana Journal, 2023)
One of the villages that is the focus of this service is Laehuwa Village located in Nias Regency, North Sumatra. Laehuwa Village has unique and distinctive potential both in terms of culture, environment, and economic potential. In this service, which was attended by 13 participants, a series of trainings were conducted for the people of Laehuwa Village to introduce and train them in the use of ChatGPT as a tool in improving digital skills. Training methods include an introduction to ChatGPT, as well as practical training in applying digital skills acquired through ChatGPT. The results of this service are expected to provide significant benefits for the people of Laehuwa Village in facing challenges in today's digital era.